2014
DOI: 10.3390/nu6104165
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sodium-Dependent Glucose Transporter 1 and Glucose Transporter 2 in the Absorption of Cyanidin-3-O-β-Glucoside in Caco-2 Cells

Abstract: Anthocyanins have multiple biological activities of benefit to human health. While a few studies have been conducted to evaluate the bioavailability of anthocyanins, the mechanisms of their absorption mechanism remain ill-defined. In the present study, we investigated the absorption mechanism of cyanidin-3-O-β-glucoside (Cy-3-G) in human intestinal epithelial (Caco-2) cells. Cy-3-G transport was assessed by measuring the absorptive and efflux direction. Inhibition studies were conducted using the pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 35 publications
1
59
0
1
Order By: Relevance
“…Previous reports from our group have shown that anthocyanins can cross MKN‐28 cell monolayers, a human gastric barrier model, probably through glucose transporters . Nevertheless, the absorption of anthocyanins also occurs throughout the gastrointestinal tract, as suggested by other in vitro studies using intestinal epithelial cells .…”
Section: Discussionmentioning
confidence: 62%
“…Previous reports from our group have shown that anthocyanins can cross MKN‐28 cell monolayers, a human gastric barrier model, probably through glucose transporters . Nevertheless, the absorption of anthocyanins also occurs throughout the gastrointestinal tract, as suggested by other in vitro studies using intestinal epithelial cells .…”
Section: Discussionmentioning
confidence: 62%
“…Extracts obtained from fermented sprouts (CUF and CUFH) contained high amount of isoflavone aglycons in which formononetin, biochanin A and genistein dominated. That chemical composition is very relevant in case of T. pratense's biological influence on human body, because isoflavones present in diet could be transported through the intestinal cell barrier in intact aglycone form [64] and are absorbed faster and in greater amounts than corresponding glucosides [65]. Earlier clinical studies have shown that the maximum recommended level for safe isoflavone intake is 75 mg/day, and a plasma concentration should not exceed 10 µM [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Osmolality was corrected to physiological levels by adapting the concentration of NaCl. The effect of the sweet taste receptor antagonist (30 µg/mL gurmarin) [32], or glucose transporter inhibitors (SGLT1 antagonist; 10 µM phloridzin [33], glucose transporter (GLUT) family antagonist; 10–20 µM phloretin [34]) was investigated by preincubation of the cells for 30 min with the respective inhibitors after which the culture medium was removed and replaced by a combination of the antagonist and the indicated carbohydrate or sweetener for three hours. The dose of gurmarin was high enough to block both TAS1R2-TAS1R3 [32] and the TAS1R3 homodimer since this dose blocked the umami taste receptor (TAS1R1-TAS1R3) and thus the common subunit of the sweet and umami taste receptor, namely TAS1R3 [23,35].…”
Section: Methodsmentioning
confidence: 99%